Hidden Inequalities in the Workplace A Guide to the Current Challenges, Issues and Business Solutions - Caven, Valerie; Nachmias, Stefanos (Palgrave Explorations in Workplace Stigma, 2018)
XIX, 341 p. 12 illus., 2 illus. in color.